Основные понятия исходной материально-правовой субстанции "суд" и их соотношение - Скакун, Ольга Федоровна; Скакун, Ольга Федорівна; Skakun, Ol'ga (My University, 2011)
In the article from the standpoint of systematic and juridical-technical analysis investigated the correlation between «judicial power», «justice», «Judiciary», «justice system» and «judgness». Revealed that the ratio of these categories in the current legislation not only violates the principle of uniformity in the use of concepts, but also introduces elements of «definitive chaos.» Demonstrated that the concept of «justice» and «judiciary» can not be regarded as synonymous, as is it is in legislation. The proposed definition of justice as a form of protection of rights, freedoms and lawful interests of citizens and their associations judiciary, which is expressed in just (benign) examine by court in established by law, procedural forms of civil, criminal, administrative cases and economic disputes, the decision on each case a reasoned decision.
Скакун О. Ф. Основные понятия исходной материально-правовой субстанции "суд" и их соотношение /О. Ф. Скакун // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C. 69-79.
Keywords: правовые категории; правосудие; судебная система; судопроизводство; правові категорії; правосуддя; судова система; судочинство; legal category; justice; judicial system; proceedings